2019
DOI: 10.1037/xlm0000687
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive memory: The mnemonic power of survival-based generation.

Abstract: Four experiments investigated the mnemonic effects of generating survival situations. People were given target words and asked to generate survival situations involving that stimulus (e.g., DOOR: "I'm in a house that's on fire, and I can escape through the door"). No constraints were placed on the generation process, other than that it must be survival-related and refer to the target stimulus. Following a series of these generation trials people were given a surprise retention test for the target words. Across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 57 publications
2
21
0
Order By: Relevance
“…For example, the word “fork” may have a similar (low) degree of semantic relatedness to the survival and moving scenarios. However, a fork may have many potential untypical functions in the survival context, such as serving as a weapon for hunting and defense, or as a tool for gardening, thus encouraging a process of semantic integration in the survival group only (see also Nairne, Coverdale, & Pandeirada, 2019 , Exp. 4).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the word “fork” may have a similar (low) degree of semantic relatedness to the survival and moving scenarios. However, a fork may have many potential untypical functions in the survival context, such as serving as a weapon for hunting and defense, or as a tool for gardening, thus encouraging a process of semantic integration in the survival group only (see also Nairne, Coverdale, & Pandeirada, 2019 , Exp. 4).…”
Section: Discussionmentioning
confidence: 99%
“…However, addressing the issue of how cognition evolved is fraught with problems -methodologically, statistically, and ethically (Powell, Mikhalevich, Logan, & Clayton, 2017). To address the ways in which we can use ancestral priorities to probe current behavioral patterns and thereby look for what variables might have been relevant to evolution (e.g., Krause et al, 2019;Nairne et al, 2019). This includes both examining the survival processing effect and exploring how animacy influences memory performance (VanArsdall, Nairne, Pandeirada, & Cogdill, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that survival processing leads to better free recall than a wide variety of other encoding techniques (see Scofield, Buchanan, & Kostic, 2018;Tay, Jonason, Li, & Ching, 2019, for reviews). Although most of the research now focuses on the proximate mechanisms that produce survival processing advantages across a range of memory tests, the original goal of developing the paradigm was to demonstrate that issues of natural selection could have strong and measurable effects on current human cognition (e.g., Nairne, Coverdale, & Pandeirada, 2019). Although the evidence for a survival processing advantage in memory is strong, I remain skeptical about the utility of thinking about this effect in terms of human natural selection (also see Krause et al, 2019;Sandry, Trafimow, Marks, & Rice, 2013).…”
Section: Survival Processingmentioning
confidence: 99%
“…This is difficult to evaluate based on the current findings, as any cognitive responses generated during encoding (and that may later act as retrieval cues) were not collected. Some work has made use of a thought generation procedure (e.g., Nairne et al, 2019;Röer et al, 2013), but this was done only during encoding. Consequently, examining the overlap between encoding and retrieval represents a promising way to further survival processing research and assess the importance of the contextual reinstatement account of greater List 1 costs following such encoding.…”
Section: Explaining the Current Findings In Terms Of Accounts Of Survival Processingmentioning
confidence: 99%